2021
DOI: 10.1111/eci.13558
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the correlation between serum asymmetric dimethylarginine, carotid atherosclerosis and ischaemic stroke

Abstract: Objective: To investigate the correlation between serum asymmetric dimethylarginine (ADMA) and the risk of ischaemic stroke and carotid atherosclerosis in adults. Methods: We systematically searched PubMed, EMBASE, Web of Science and other databases for relevant studies on serum ADMA and ischaemic stroke or carotid atherosclerosis, which were published from December 1980 to December 2019. The quality of the included studies was evaluated according to the Cochrane system evaluation standard. The difference in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Asymmetric dimethylarginine (ADMA) is a derivate product from the normal protein metabolism, being an endogenous inhibitor of nitric oxide (NO) synthesis in the vascular endothelium [88].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asymmetric dimethylarginine (ADMA) is a derivate product from the normal protein metabolism, being an endogenous inhibitor of nitric oxide (NO) synthesis in the vascular endothelium [88].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that increased ADMA levels are associated with the atherosclerosis process and endothelial dysfunction [88,90].…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic IR was found to be an independent risk factor for GSD ( Biddinger et al, 2008 ; Chang et al, 2008 ); therefore, we infer that ADMA plays a promoting role in the process of gallstone development. ADMA is an endogenous inhibitor of nitric oxide (NO) synthetase, and endothelial dysfunction due to reduced bioavailability of nitric oxide (NO) is a risk factor for atherogenesis ( Qin et al, 2021 ), myocardial infarction ( Mannino et al, 2019 ), and chronic kidney disease ( Shah et al, 2021 ). At the same time, studies have shown that GB hypomotility plays a key role in gallbladder (GB) normal relaxation ( Chen et al, 1997 ; Swartz-Basile et al, 2000 ), while GB hypomotility is also a required factor for gallstone pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Janes et al [30] showed that ADMA levels are associated with cerebral small vessel disease in asymptomatic patients. A recent review showed that high ADMA levels were associated with carotid atherosclerosis, which is a risk factor for ischemic stroke [31]. Still, some studies suggest that ADMA levels are not associated with stroke [32][33][34].…”
Section: Discussionmentioning
confidence: 99%